Analisis Kelayakan Usahatani Madu Hutan di Kelurahan Balocci Baru Kecamatan Balocci Kabupaten Pangkajene dan Kepulauan - Roslina Hamzah; Abd. Asis Pata; Andi Nur Imran (Jurnal Agribis, 2022)
The purpose of this study was to determine the amount of forest honey farming income in Balocci Baru Village, Balocci District, Pangkajene Regency and Islands, and to determinan the feasibility of forest honey farming in Balocci Baru Village, Balocci District, Pangkajene Regency and Islands. This research was conducted in Balocci Baru Village, Balocci District, Pangkajene Regency and Islands, where this research was conducted from March to June 2022. The method of determining the sample is using the saturated sample method with a sample of 10 samples. The analytical method used in this research is qualitative and quantitative analysis, income and feasibility formulas. The results of the research can be seen that the amount of income obtained from forest honey farming in Balocci Baru Village, Balocci District, Pangkajene Regency and Islands is Rp. 68.995,750 with an average income of Rp 6.899.575/year. The result of the calculation of the R/C ratio, which is 26,5>1, means the fotest honey farming in Balocci Baru Village, Balocci District, Pangkajene Regency and Islands is feasible.